ANALYSIS OF TRANSFORMATIONAL LEADERSHIP IN THE IMPLEMENTATION OF EMPLOYEE DISCIPLINE IN BAPPELITBANGDA, WAJO DISTRICT - Asmanurhidayani; Saniyyah Putri Salsabila Said; Syamsiar; Nurcaya (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
ANALYSIS OF TRANSFORMATIONAL LEADERSHIP IN THE IMPLEMENTATION OF EMPLOYEE DISCIPLINE IN BAPPELITBANGDA, WAJO DISTRICT